2003
DOI: 10.1007/s00213-003-1472-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice

Abstract: These studies show that GIRK2 deletion reduced ethanol's impact in tasks that are commonly used to index the drug's rewarding and aversive effects. These findings could reflect either a learning/memory deficit or decreased sensitivity to ethanol's motivational effects in null mutant mice. The latter interpretation is more consistent with previous data showing that knockout mice consume higher doses of ethanol than wild type mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…Interestingly, GIRK2 knockout mice show reduced ethanol-induced conditioned taste aversion and conditioned place preference and are less sensitive than wild-type mice to some of the acute effects of ethanol, including anxiolysis, habituated locomotor stimulation, and acute handlinginduced convulsions (Hill et al, 2003). In the present study, atomoxetine inhibited ethanol-induced GIRK1/2 currents, suggesting that it may suppress some GIRK-related effects of ethanol.…”
Section: Discussionsupporting
confidence: 44%
“…Interestingly, GIRK2 knockout mice show reduced ethanol-induced conditioned taste aversion and conditioned place preference and are less sensitive than wild-type mice to some of the acute effects of ethanol, including anxiolysis, habituated locomotor stimulation, and acute handlinginduced convulsions (Hill et al, 2003). In the present study, atomoxetine inhibited ethanol-induced GIRK1/2 currents, suggesting that it may suppress some GIRK-related effects of ethanol.…”
Section: Discussionsupporting
confidence: 44%
“…The interaction between GIRK2 and neurobiological stress systems is suggestive of a mechanism by which the reinforcing effects of alcohol develop during periods of environmental stress. Indeed, Hill et al (2003) found that they were unable to establish a place preference for ethanol in GIRK2-null mice, which confirms the notion that GIRK2 is important for alcohol reward. In support of this, we find that genetic variation in GIRK2 is associated with the initiation of alcohol abuse in adolescents when psychosocial stress is present, and in addition, an association is also found with the maintenance of alcohol dependence in adults.…”
Section: Discussionsupporting
confidence: 62%
“…They found that they could not establish a place preference or conditioned taste aversion for 2-3 g/kg of ethanol in mice lacking GIRK2 channels (Hill et al, 2003), concluding that GIRK2 may be mediating the reinforcing and/or aversive motivational aspects of ethanol action. In human beings, only one study has examined GIRK2 and addictive phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol modulation of GIRK channels regulates neuronal excitability in the brain's reward circuit (11) and underlies forms of alcohol addiction (6,(8)(9)(10)36). Here, we uncovered previously undescribed principles governing alcohol modulation of GIRK channels.…”
Section: Discussionmentioning
confidence: 91%
“…G-proteingated inwardly rectifying K + (GIRK or Kir3) channels are activated by concentrations of ethanol relevant to human consumption (18 mM ethanol or 0.08% blood alcohol level) (3)(4)(5) and have been found to play a key role in alcohol-related disorders (6)(7)(8)(9). For example, mice lacking GIRK2 (or Kir3.2) channels self-administer more ethanol and fail to develop conditioned place preference for ethanol, compared with wild-type (WT) littermates (6,10). These results support a model in which ethanol may have lost its target in GIRK knockout mice, thus failing to elicit behaviors associated with ethanol consumption.…”
mentioning
confidence: 99%